2003
DOI: 10.1191/0961203303lu331oa
|View full text |Cite
|
Sign up to set email alerts
|

Use of a new fluorescence immunoassay to detect anti-dsDNA antibodies is more correlated with disease activity and complement than the ELISA method in SLE patients

Abstract: To determine whether the serum levels of anti-double strand DNA (anti-dsDNA) autoantibodies detected using a newly developed fluorescence immunoassay (FIA) in patients with systemic lupus erythematosus (SLE) correlated more with clinical parameters, such as SLE disease activity index (SLEDAI), complement and the occurrence of nephritis when compared with traditional enzyme-linked immunosorbent assay (ELISA), we prospectively collected 124 serum samples from 31 patients who had juvenile-onset SLE and were regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…20 Whereas both assays show the lowest specificity for lupus nephritis (54%), assay 1 has a better specificity for the whole SLE group. Assay 4 is a relatively new automated method, extensively studied in the last three years [21][22][23][24] mainly because of its putative ability to detect preferentially high avidity aDNA-Ab. In agreement with our data, most studies revealed sensitivities for SLE between 40 and 64%, combined with specificities usually Ͼ90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Whereas both assays show the lowest specificity for lupus nephritis (54%), assay 1 has a better specificity for the whole SLE group. Assay 4 is a relatively new automated method, extensively studied in the last three years [21][22][23][24] mainly because of its putative ability to detect preferentially high avidity aDNA-Ab. In agreement with our data, most studies revealed sensitivities for SLE between 40 and 64%, combined with specificities usually Ͼ90%.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, most studies revealed sensitivities for SLE between 40 and 64%, combined with specificities usually Ͼ90%. [21][22][23][24] However, employing a special method to measure the Ab avidity directly 25 it could be shown, that only 45% of the aDNA-Ab detected by assay 4 represent really high avidity ones. 21 This could be in agreement with our observation, that the specificity, PPV and NPV for lupus nephritis are not remarkable higher than those found for assay 1.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-double stranded DNA (anti-dsDNA) antibodies are the hallmark antibodies of SLE [ 12 ]. Anti-dsDNA antibodies are correlated with disease activity [ 13 ] and involved in the pathogenesis of SLE [ 14 ]. Anti-dsDNA antibodies presented in the blood before disease onset [ 15 ] and administration of anti-dsDNA antibodies from SLE patients into NZBWF1/J mice resulted in accelerated lupus [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 The latter characteristic is crucial for using it as a screening assay. However, utility for detecting lupus flares had not previously been demonstrated, except in one recent work by Chen et al, 12 where they studied 31 patients with juvenile-onset SLE.…”
Section: Discussionmentioning
confidence: 99%